Personality factors in relation to students preparedness toward workplace / Nek Kamal Yeop Yunus - Yeop Yunus, Nek Kamal (2002)
Employees' personality have great impact on their behavior and performance at the workplace. Since, the workplace has undergone significant changes, graduating polytechnic students need to prepare themselves with technical skills and good personality in order to be successful in the workplace. The purpose of the study was to investigate if there was any positive relationship between commerce student personality factors with their preparedness towards workplace. It was hypothesized that students with high self esteem, self monitoring and locus of control would have performed successfully in terms of industrial training performance, academic achievement and perceived ability to perform at workplace. The methodological approach was by systematic random sampling using a structured, 68 items questionnaire which was distributed to 252 commerce students in Malaysian polytechnics. Data collected were analyzed using SPSS and it was found that there was a positive significant relationship between self monitoring and students perceived ability to perform at workplace. Commerce students need the personality factors in their business tasks which can be developed by proper training. It was recommended that further research on this subject be conducted with larger sample size and by taking into consideration of other factors such as teaching methods, length of training and the relevancy of the course contents.